Hidden aspects of meaning in the phonetic layer of Haft-Peykar - Gholamhosehn Madadi; Ebrahim Estaji; Azam Estaji; ali tasnimi (مطالعات زبانی و بلاغی)
In the process of achieving literariness, language moves away from its usual form, and linguistic elements in the text go beyond conventional types for an artistic usage. In outstanding literary works, there is a special link between the content and the way linguistic units are used in different layers. Haft Peykar is also one of the unique works, in which Nezami used various linguistic capacities at various levels to strengthen the content and create a kind of stylistic distinction in this masterpiece. A literary work consists of intertwined layers. Therefore, analyzing the text of Haft Peykar with a layered stylistic approach is a proper way to discover the linguistic capacities and artistic function of language units. Accordingly, the role of each layer in the production and transmission of the message is specified in the analysis of that layer. Among the linguistic layers, the phonetic layer is considered as an introduction to language analysis since sound is the first tangible sign of language. In addition to their role in increasing musicality, the components that can be studied for their external, internal, spiritual, and lateral music have found an artistic function concerning the meaning in the Nezami’ words so that even the smallest linguistic units play a significant role in producing and transmitting the message of the work. The rhythmic capacities in the external music cause the music that governs the different spaces of the text to be consistent with the content and the induction of meaning. In lateral music, the purposeful selection of rhyme scheme Rhyme scheme and the resulting melody facilitate signification, production and transfer of meaning from the sound level to the content. Literary techniques are used in the inner music similar to perceptual coding, which leads to readers’ further contemplation and also creates a kind of hypertext signification. The connection of spiritual music with content and the creation of marginal meanings is a novel method that has bestowed a kind of stylistic distinction to Nezami’s words.